An Analysis of Teacher's Strategies in Teaching Reading Comprehension of Narrative Text: A Descriptive Study on Grade 10 Students of SMA Negeri 1 Semparuk in 2022/2023 Academic Year) - Nurbaiti; Sumarni; Husin Syarif; Rosnija Eni; Wardah (Kirana Publisher (KNPub), 2023)
This study was aimed to find out the teaching strategies that used by the teacher in teaching reading comprehension of narrative text in X grade of SMA Negeri 1 Semparuk. The participant of this is research is an English teacher who has been teaching for about 18 years in SMA Negeri 1 Semparuk. A descriptive qualitative design was employed in this research by using semi-structured interview and observation as the technique of data collection. The findings of the research showed that the teacher used two strategies in teaching reading comprehension of narrative text they were small group discussion strategy and Questions and Answers Relationship (QnAR) strategy. The teacher used small group discussion strategy in helping students to get the same opportunity to understand the material. Another strategy was Questions and Answers Relationship (QnAR) strategy used in order to obtain students’ critical thinking. Furthermore, QnAR strategy was used in measuring and knowing students’ understanding about the material. In addition, the finding showed that these strategies gave good impact to influence students’ reading comprehension ability of narrative text. It can be seen from the teaching learning process and the score of the individual evaluation test.